EFFECT OF INNOPROVET PROBIOTIC ON MEAT QUALITY OF EGG LAYER CHICKEN (Web of Teachers: Inderscience Research, 2024)
This article presents the results of veterinary sanitary assessment and composition study of the meat of chickens and the meat obtained from them when the probiotic "Innoprovet" is given to laying hens.